Evaluating the effectiveness and safety of empagliflozin versus liraglutide in managing diabetic dyslipidemia: An observational study - Motakatla Usha Rani; Chitra Karuppiah; Penupothu Sree Nagamani (Asian Journal of Medical Sciences, 2024)
Background: Diabetic dyslipidemia poses a significant risk factor for cardiovascular complications in patients with diabetes mellitus. Empagliflozin and liraglutide are two commonly used medications in diabetes management, yet their comparative efficacy and safety in treating diabetic dyslipidemia remain under-explored. Aims and Objectives: This study aimed to assess the effectiveness and safety of Empagliflozin versus liraglutide in managing diabetic dyslipidemia. Materials and Methods: The study enrolled 100 participants with diabetes and dyslipidemia, divided equally into empagliflozin and liraglutide treatment groups. Baseline characteristics, including age, gender distribution, ethnicity, and duration of diabetes, were assessed and compared between the groups. Lipid profiles, encompassing total cholesterol, low-density lipoprotein (LDL) cholesterol, high-density lipoprotein (HDL) cholesterol, and triglycerides, were evaluated at baseline and after 6 months of treatment. Safety outcomes, such as the occurrence of mild gastrointestinal symptoms, hypoglycemia, and serious adverse events, were also monitored. Results: Both treatment groups exhibited comparable baseline characteristics. Following 6 months of treatment, both empagliflozin and liraglutide demonstrated significant improvements in lipid profiles. Reductions in total cholesterol, LDL cholesterol, and triglycerides, along with increases in HDL cholesterol, were observed in both groups. Moreover, there were no significant differences in the occurrence of adverse events between the two treatment groups, indicating similar safety profiles. Conclusion: This study provides evidence supporting the effectiveness and safety of empagliflozin and liraglutide in managing diabetic dyslipidemia. These findings highlight the potential of both medications as viable therapeutic options for patients with diabetes and dyslipidemia.